Endoscopic Management of Weight Regain in the Bariatric Patient - Dolan, Russell D.; Schulman, Allison R. (Digestive Disease Interventions, 2021)
Despite initial weight loss following bariatric surgery, weight recidivism is common. While weight regain is multifactorial and includes behavioral, psychosocial, and medical causes, changes in anatomy also play a role. Dilation of the gastrojejunal anastomosis following Roux-en-Y gastric bypass and enlargement of the gastric sleeve following sleeve gastrectomy are both important considerations. Historically, surgical revision has been performed to address weight regain; however, morbidity and mortality are not insignificant. Over the past decade, a variety of endoscopic approaches have been described for weight recidivism, several of which have proven to be safe, effective, and durable. This article will review each of these techniques in detail.
Keywords: weight regain; transoral outlet reduction; argon plasma coagulation; endoscopic suturing; endoscopic revision